Winning Ways of Women Coaches - Reynaud, Cecile (Human Kinetics Library, 2023)
We’ve entered a new era of women in coaching. Women coaches across the globe have triumphed, using their expertise, experience, and sustained success to break down barriers and establish new standards of excellence in their coaching roles. Winning Ways of Women Coaches reflects this new era. Some of the most exceptional women coaches in the world have contributed to this groundbreaking book, each examining a different coaching topic from her unique viewpoint. Representing 15 different sports—including professional football and baseball—and earning more than 50 national championships and dozens of world and Olympic titles, these coaching pioneers provide the acumen and inspiration to succeed in the coaching profession: Lonni Alameda Rachel Balkovec Becky Burleigh Denise Corlett Melody Davidson Kelly Inouye-Perez Roselee Jencke Valorie Kondos Field Melissa Luellen Teri McKeever Missy Meharg Felecia Mulkey Carla Nicholls Carol Owens Carolyn Peck Ellen Randell Nancy Stevens Tara VanDerveer Amber Warners Jen Welter Edited by volleyball coaching legend Cecile Reynaud, PhD, the book equips current and aspiring women coaches with innovative strategies and real-world insights to address common coaching challenges, build and maintain successful sport programs, foster player engagement and growth, and further their coaching careers. In addition, contributing coaches weave a common thread throughout the chapters by discussing the importance of building team chemistry and their own approaches to fostering a team culture. Whether you’re searching for proven coaching techniques, creative new approaches, or sage troubleshooting advice, Winning Ways of Women Coaches will prove to be your most valuable resource. After reading this book, you’ll discover that it’s your ability to instruct, develop, and care for your athletes—not just your knowledge of Xs and Os—that will propel your career and separate you from the rest. Showcasing women coaches who have reached the top of their profession and embodying the idea of “If she can see it, she can be it,” Winning Ways of Women Coaches will reinvigorate current coaches and inspire would-be coaches to make the leap into coaching